Preparation, characterization and comparative electrochemical studies of MgMXMn2-XO4 (x=0, 0.5; M= Ni/Co). Issue 10 (July 2019) - Banu, A.; A.Sakunthala; Thamilselvan, M.; Kumar, P. Senthil; Suresh, K.; Ashwini, S.
Abstract: In this study, the structural, electrical and electrochemical properties of the compounds MgMx Mn2-x O4 [M = Ni/Co: x = 0, 0.5] were investigated by preparing the materials by the citric acid assisted simple, cost effective sol-gel method. X-ray Diffraction (XRD) confirmed that Ni/Co doping created a phase transition of MgMn2 O4 from tetragonal spinel-structure with a space group of I 4 1 / amd to a cubic spinel structure with a space group of Fd-3m . HRTEM and SAED analysis showed the bare compound to be polycrystalline and doped compounds to be single crystalline in nature. SEM analysis showed the agglomerated submicron sized particles for all the three compounds. The electrical properties of the compounds have been investigated through AC impedance spectroscopy. The electrical conductivity of the bare compound MgMn2 O4 was found to be 5.09 × 10 −6  S/cm at 583 K. Cyclic Voltammetry (CV) and Galvanostatic Charge-Discharge (GCD) studies made by the three electrode system shows that all the samples under study could undergo reversible redox reactions in the aqueous magnesium nitrate solution. MgMn2 O4 sample exhibited highest specific discharge capacity of 263 mAh/g at the current density of 30 mA/g.